2009
DOI: 10.3758/app.71.7.1649
|View full text |Cite
|
Sign up to set email alerts
|

Tracking time with song and count: Different Weber functions for musicians and nonmusicians

Abstract: Participants reproduced target intervals of 6-24 sec with finger taps, with target intervals presented before each of 30 reproductions. During the presentation of the target and reproduction, nonmusician participants were asked to count, sing, or do nothing. In another part of the experiment, musicians were asked to count or sing. Segmentation, either by song or count, minimized deviations from targets and reduced the coefficient of variation (CV) to one third of the nonmusicians' CVs in the no-segmentation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 32 publications
5
37
0
1
Order By: Relevance
“…Explicit count of numbers reduces very much the Weber fraction from 1 to 2 s, but this fraction remains stable from 2 to 4 s ( [56], Experiment 2). Some human data show that the Weber fraction remains constant, even without counting, for intervals up to 24 s for an interval reproduction task [57,58], and that this fraction is even reduced with longer intervals when explicit counting is adopted [58]. The reduction of the Weber fraction with longer intervals was observed in Grondin and Killeen [57] only with musicians, not with non-musicians, and this observation applies with both the use of explicit counting and singing for segmenting time.…”
Section: Recent Data: Extended Rangementioning
confidence: 82%
See 2 more Smart Citations
“…Explicit count of numbers reduces very much the Weber fraction from 1 to 2 s, but this fraction remains stable from 2 to 4 s ( [56], Experiment 2). Some human data show that the Weber fraction remains constant, even without counting, for intervals up to 24 s for an interval reproduction task [57,58], and that this fraction is even reduced with longer intervals when explicit counting is adopted [58]. The reduction of the Weber fraction with longer intervals was observed in Grondin and Killeen [57] only with musicians, not with non-musicians, and this observation applies with both the use of explicit counting and singing for segmenting time.…”
Section: Recent Data: Extended Rangementioning
confidence: 82%
“…Some human data show that the Weber fraction remains constant, even without counting, for intervals up to 24 s for an interval reproduction task [57,58], and that this fraction is even reduced with longer intervals when explicit counting is adopted [58]. The reduction of the Weber fraction with longer intervals was observed in Grondin and Killeen [57] only with musicians, not with non-musicians, and this observation applies with both the use of explicit counting and singing for segmenting time. Note finally that, when a series of intervals is produced sequentially, the Weber fraction increases with longer intervals (up to 24 s-non-musician participants) in spite of the use of explicit counting [59].…”
Section: Recent Data: Extended Rangementioning
confidence: 82%
See 1 more Smart Citation
“…When typical numerically developed individuals need to perform supra-second timing estimation, they often rely on counting strategies (Brown et al, 1995;Gilaie-Dotan, Kanai & Rees, unpublished observations;Gilliland & Martin, 1940) that allow them to estimate slightly better supra-second intervals (Grondin et al, 1999(Grondin et al, , 2004Rakitin et al, 1998; but see . Studies investigating the effectiveness of counting found that counting is advantageous for estimating intervals longer than 1.18 s but not for sub-second intervals (Grondin et al, 1999(Grondin et al, , 2004 and that musicians with extensive musical training reproduce supra-second intervals more accurately than non-musicians, whether relying on counting or singing (Grondin & Killeen, 2009). Due to this common tendency to use counting for estimating supra-second intervals, studies examining supra-second timing mechanisms often use a dual task to interfere or prevent counting (see Rakitin et al, 1998), or specifically instruct participants not to count when timing Rakitin et al, 1998;Treisman, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Grondin and Killeen (2009) compared musicians' and nonmusicians' accuracy in an interval reproduction task that involved counting and singing during the intervals. Nonmusicians' reproduction accuracy was much improved by these filler activities, and musicians performed even better than nonmusicians.…”
mentioning
confidence: 99%